Pendampingan Penerapan Metode Lalaran dan Tikroran dalam Penguatan Hafalan Kitab Alfiyah Program Satu Tahun Ajaran di Pondok Pesantren Nurul Qur’an Ponorogo - Rifatur Rosidah; Samsudin (Social Science Academic, 2025)
This study aims to analyse the implementation of the lalaran and tikroran methods in strengthening the memorization of Ibn Malik’s Alfiyyah within the one-year program at Pondok Pesantren Nurul Qur’an. The lalaran method refers to the collective recitation of the verses with a specific rhythm repeated continuously to facilitate memorization, while tikroran is not much different from lalaran, except that it involves not only repetition of the verses but also their translation (locally referred to as murod). This research employs a qualitative approach whit a case study design. Date were obtained through observation, in-depth interviews, and documentation. The findings indicate that lalaran, conducted daily before and after study sessions, serves as an effective activity to strengthen students’memory. The application of this method aims to accelerate the mastery of verses while enhancing the understanding of grammatical rules in Alfiyyah through tikroran translation. Both methods demonstrate a significant impact in reinforcing students’ long-term memorization. Supporting factors include the motivation provided by the caretakers and teaching staff, the solidarity among students, and a conductive learning environment. The main challenges, however, lie in the differences in students’memorization abilities and limited time allocation, as the program for studying Alfiyyah at Pondok Pesantren Nurul Qur’an is designed to be completed within one academic year. In conclusion, the lalaran and tikroran methods are effective methods to strengthen students’memorization within a relatively short learning period.